Intra-European lifestyle migration of German (pre)retirees to rural Spain: a contribution to rural development in times of the financial and real-estate crisis? The migrants’ point of view. - Weidinger, Tobias; Kordel, Stefan (European rural peripheries revalued: Governance, actors, impacts, 2016)
This article concerns lifestyle and leisure-oriented migration of German (pre)retirees aged 50+ to the hinterland of the Spanish Costa Blanca. Against the backdrop of the current financial and real estate crisis it is discussed, how migrants, addressed as relatively affluent, contribute to rural development in terms of economic and social practices. Deriving from migrants' biographies, analyses take an individual perspective for a deeper understanding of practices due to their desired way of living. Results show that the migration decision, which is inspiured by idealised notions of the countryside, i.e., a rural idyll, and repeatedly negotiated through meaningful practices in post-migration lives. In light of the crisis, they both persist on and alter practices with regard to consumption or civil commitment in order to support local population and thus uphold idyllic notions of rurality. Thereby, everyday practices also reflect their relatively affluent status, which, from their perspective, contribute to rural development.